2D InSe Self‐Powered Schottky Photodetector with the Same Metal in Asymmetric Contacts. Issue 35 (9th November 2022) - Chen, Jinping; Zhang, Zhen; Feng, Jiying; Xie, Xiaoyu; Jian, Aoqun; Li, Yuanzheng; Guo, Heng; Zhu, Yizhi; Li, Zhuxin; Dong, Jianqi; Cui, Qiannan; Shi, Zengliang; et al.
Abstract: Self‐powered photodetectors (SPPDs) are generally carried out in multilayered heterostructures with different semiconductors or in Schottky junctions with different metal electrodes. It is interesting to build an SPPD using metal–semiconductor–metal (MSM) structures with the same type of metal electrodes. Here, an SPPD is fabricated facilely by stacking a piece of irregular InSe nanosheet on a pair of Au electrodes with asymmetric van der Waals contacts. The SPPD performs a high responsivity of 0.103 A W −1, a high on‐off current ratio over 10 4, a high detectivity of 1.83 × 10 10 Jones, a fast response time of 1 ms and a broadband sensing spectrum ranging from 300 to 1000 nm under zero bias. A series of characterization and working mechanism analysis demonstrate the contribution of the asymmetric Schottky barrier heights and contact geometries in Au–InSe junctions to the self‐powered performance of the detector. This work offers an effective scheme to construct high‐performance SPPDs in simple architecture and processing for potential optoelectronic device applications. Abstract : The Au/InSe/Au van der Waals Schottky structures with a pair of the Au electrodes are demonstrated to perform a high‐performance self‐powered broadband photoresponse due to the asymmetric Schottky barrier heights and contact geometries in Au–InSe junctions.